Determination of the antioxidant capacity of two seagrass species according to the extraction method - Kethia L. González; Richard Gutiérrez; Yasnay Hernández; Olga Valdés-Iglesias; María Rodriguez (GarVal Editorial Ltda., 2016)
Context: There is a wide variety of methods for obtaining of plant extracts that enable a good yield of bioactive metabolites. For several years, extractive techniques have been perfected for obtaining natural extracts with powerful pharmacological properties. Aims: To determine the influence of various extraction methods (infusion, decoction, microwave, maceration with heat and agitation, and constant heat and agitation) on the content of solids, phenolic compounds and antioxidant capacity of marine angiosperms Thalassia testudinum Banks ex König (Hyrocharitacea) and Syringodium filiforme kützing (Cymodoceaceae). Methods: The soluble solids content was determined by the gravimetric method; total phenolic content, using Folin-Ciocalteu method, and the antioxidant capacity by 2,2-diphenyl-1 picrylhydrazyl (DPPH) method. Results: Results showed the effectiveness of extraction by decoction for T. testudinum and by microwave for S. filiforme, among the methods that use water as the extraction solvent. In the case those that use the hydroalcoholic mixture as solvent extraction, maceration with agitation and heat extraction showed the higher yields of soluble solids and total polyphenols, as well as a higher antioxidant activity for both species. Conclusions: Results showed the effectiveness of extraction by decoction for T. testudinum and by microwave for S. filiforme, among the methods that use water as extraction solvent. In the case those that use hydroalcoholic mixture as solvent extraction, maceration with agitation and heat extraction showed the higher yields of soluble solids and total polyphenols, as well as a higher antioxidant activity for both species.